Transfer from implicit to explicit phonological abilities in first and second language learners*. Issue 4 (27th April 2016) - JANSSEN, CARESSA; SEGERS, ELIANE; MCQUEEN, JAMES M.; VERHOEVEN, LUDO
Abstract : Children's abilities to process the phonological structure of words are important predictors of their literacy development. In the current study, we examined the interrelatedness between implicit (i.e., speech decoding) and explicit (i.e., phonological awareness) phonological abilities, and especially the role therein of lexical specificity (i.e., the ability to learn to recognize spoken words based on only minimal acoustic-phonetic differences). We tested 75 Dutch monolingual and 64 Turkish–Dutch bilingual kindergartners. SEM analyses showed that speech decoding predicted lexical specificity, which in turn predicted rhyme awareness in the first language learners but phoneme awareness in the second language learners. Moreover, in the latter group there was an impact of the second language: Dutch speech decoding and lexical specificity predicted Turkish phonological awareness, which in turn predicted Dutch phonological awareness. We conclude that language-specific phonological characteristics underlie different patterns of transfer from implicit to explicit phonological abilities in first and second language learners.